Structural insights into hedgehog ligand sequestration by the human hedgehog-interacting protein HHIP. - Bishop, B; Aricescu, A; Harlos, K; O'Callaghan, C; Jones, E; Siebold, C (2009)
Hedgehog (Hh) morphogens have fundamental roles in development, whereas dysregulation of Hh signaling leads to disease. Multiple cell-surface receptors are responsible for transducing and/or regulating Hh signals. Among these, the Hedgehog-interacting protein (Hhip) is a highly conserved, vertebrate-specific inhibitor of Hh signaling. We have solved a series of crystal structures for the human HHIP ectodomain and Desert hedgehog (DHH) in isolation, as well as HHIP in complex with DHH (HHIP-DHH) and Sonic hedgehog (Shh) (HHIP-Shh), with and without Ca2+. The interaction determinants, confirmed by biophysical studies and mutagenesis, reveal previously uncharacterized and distinct functions for the Hh Zn2+ and Ca2+ binding sites--functions that may be common to all vertebrate Hh proteins. Zn2+ makes a key contribution to the Hh-HHIP interface, whereas Ca2+ is likely to prevent electrostatic repulsion between the two proteins, suggesting an important modulatory role. This interplay of several metal binding sites suggests a tuneable mechanism for regulation of Hh signaling.